2018
DOI: 10.5194/acp-2018-704
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular characterization of organic aerosols in the Kathmandu Valley, Nepal: insights into primary and secondary sources

Abstract: Abstract:Organic atmospheric aerosols in the Hindu Kush-Himalayan-Tibetan Plateau region are still poorly characterized. To better understand the sources and formation processes of the primary organic aerosols (POA) and secondary organic aerosol (SOA) in the foothills region of the central Himalaya, we studied atmospheric aerosol samples collected over a one-year period from April 2013 to April 2014 at the Atmos. Chem. Phys. Discuss., https://doi

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…Satellite data and ground‐based aerosol measurements have confirmed that the increase of BC mass concentrations in the northern India during wintertime is mainly related to the dense crop residue and biomass burning (Sarkar et al, 2018). Because of a lack of electrical power, biomass burning is the major energy sources for household heating and cooking in Kathmandu in winter (Chen et al, 2015), contributing to the high concentrations of BC and OC (Wan et al, 2019). These emission sources coupled with vehicular emissions in the cities significantly contributed to the haze formation in the South Asia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Satellite data and ground‐based aerosol measurements have confirmed that the increase of BC mass concentrations in the northern India during wintertime is mainly related to the dense crop residue and biomass burning (Sarkar et al, 2018). Because of a lack of electrical power, biomass burning is the major energy sources for household heating and cooking in Kathmandu in winter (Chen et al, 2015), contributing to the high concentrations of BC and OC (Wan et al, 2019). These emission sources coupled with vehicular emissions in the cities significantly contributed to the haze formation in the South Asia.…”
Section: Resultsmentioning
confidence: 99%
“…Based on our observations, the local residents often use various biomass for daily cooking and heating and also burn household waste at a garbage disposal station out of the village in weekend. One recent study reported the intense emission sources for the high concentrations of carbonaceous aerosols (monthly average OC in TSP: 62.8 μg/m 3 , monthly average EC in TSP: 11 μg/m 3 ) in the Kathmandu Valley in winter (Wan et al, 2019). In addition, the narrow channels are subject to being receptor areas for particle number concentrations of carbonaceous aerosols from wide and flat areas like the South Asia.…”
Section: Resultsmentioning
confidence: 99%
“…This combination leads to high concentrations of PM, including black carbon (BC) and organic carbon (OC) (ref. [3][4][5][6][7] and gaseous air pollutants like volatile organic compounds (VOC), ozone (O 3 ), and carbon monoxide (CO). 5,[8][9][10][11][12] Aerosol concentrations have increased continuously over the last 15 years in the Kathmandu Valley, 13 and these elevated concentrations have contributed to severe adverse health impacts.…”
Section: Introductionmentioning
confidence: 99%
“…S1 †), the elevated concentrations of anhydrosugars in the dry I and dry II seasons could be due to enhanced biomass burning in northeastern and southeastern Thailand, including agricultural waste burning and wood burning for cooking. 66,67 The ratios of levoglucosan/mannosan (L/M) and levoglucosan/(mannosan + galactosan) [L/(M + G)] have been proposed as indicators for different types of biomass fuels. 64,68 The average L/M and L/(M + G) ratios have been reported as 2-6 and 1.8-7 for sowoods, 69-72 13-52 and 4.5-17.6 for hardwoods, 69-73 12.7-60.7 and 6.4-52.4 for crop residue combustion, 53 and 2-33.3 and 1.7-9.5 for herbaceous plants, 58 respectively.…”
Section: Papermentioning
confidence: 99%